STUDY OF INTERMODAL INTEGRATION IN DUKUH ATAS TOD AREA - Arghia, Dinanti
High mobility in the metropolitan area causes transportation problems such as congestion. The transit-oriented development (TOD) areas are thought to be the solution in fulfilling people's needs to commute in the cities efficiently through intermodal integration. This study mainly focuses on Dukus Atas area, which becomes the intersections of five different public transportation modes, namely MRT, Railink Airport Train, KRL Commuter line, Transjakarta BRT, and LRT. Although the transit-oriented development already implemented, the integration of five different transportation modes is still becoming a problem in Dukuh Atas TOD Area. This research aims to investigate the existing problem in the integration area. Furthermore, this research also analyzes the perception and the preferences of the passengers' modes in Dukuh Atas TOD Area. The problems of the existing integration are analyzed through observation, while the preferences of the passengers' modes are analyzed through questionnaires. The scope of the research is only limited to the integration component, which encompasses physical, schedule, fares, ticket systems, and information. This research uses quantitative analysis by using cross tabulation and binary logistic regression to determine the result. A crosstabulation analysis is conducted to determine the relationship between the variables in the integration component. Moreover, the Binary Logistic Regression Analysis is utilized to discover which variables in the integration component have an impact on the obstacles which occur in Dukuh Atas TOD Area. The result shows that the integration between the modes in Dukuh Atas TOD Area has not connected yet. Moreover, the perception and preferences of the passenger modes highlight the three most influential barriers for the integration in Dukuh Atas TOD Area namely age of the passenger, the total cost of the trip and schedule conditions.